Experimental study on the flow and thermal characteristics of two-phase leakage through micro crack. (25th June 2019) - Zhang, J.; Yu, H.; Wang, M.J.; Wu, Y.W.; Tian, W.X.; Qiu, S.Z.; Su, G.H.
Highlights: This study focus on the characteristics of two-phase critical flow through slits. Narrow (as low as 50 μm) and short (1–2 mm) flow passages (L/D = 4–21) were adopted. Influence of conditions and morphologies on flow characteristics were obtained. Dimensionless number β is proposed, β = 15 is applied to distinguish flow phenomena. Correlations are developed to predict the flow rate, with reasonable precision. Abstract: Better understanding of the leakage characteristic through thin-walled pipes is of great importance to maintain the integrity of reactor pressure boundary. This experimental study focuses on the characteristics of two-phase critical flow through short slits ( L/d = 4–21), and the test pressure covers the range of 0.1–10.0 MPa. Cracks with small passage opening (as low as 46.5 μm) were adopted to better simulate the real crack, where both axial and circumferential crack were considered. Therefore the test database was enlarged. Influences of stagnation conditions and crack morphologies were analyzed. The flow mechanism was explained on how flash decides the flow rate by affecting flow pattern and choking: circumferential crack shows a higher leakage than axial crack, due to a weaker choking phenomenon; the flow pattern transition is discovered at low subcooling degree. A dimensionless number β, indicating the fraction of flashing, was proposed and two different flow phenomenon stages were identified and distinguished by β = 15. Besides, correlations were developed for the flow rate through short slits, showing a reasonable accuracy in predicting the test data both in this study and from literature.